2017
DOI: 10.1093/femsre/fux012
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for clinical use of engineered human host defense antimicrobial peptides

Abstract: Infectious diseases caused by bacteria, viruses or fungi are among the leading causes of death worldwide. The emergence of drug-resistance mechanisms, especially among bacteria, threatens the efficacy of all current antimicrobial agents, some of them already ineffective. As a result, there is an urgent need for new antimicrobial drugs. Host defense antimicrobial peptides (HDPs) are natural occurring and well-conserved peptides of innate immunity, broadly active against Gram-negative and Gram-positive bacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 213 publications
(293 reference statements)
0
115
0
2
Order By: Relevance
“…Next, we investigated possible carbohydrate moieties on herpesviridae that Aβ may target. Classical heparin-binding AMPs target viral glycoproteins, including LL-37 (Pachon-Ibanez et al, 2017) and θ and α -defensins (Hazrati et al, 2006). Immobilized HSV1 was pre-incubated with antibodies to herpesviridae glycoproteins B (gB), C (gC), D (gD), E (gE), H (gH), or G (gG) prior to incubation with conditioned CHO-CAB media.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we investigated possible carbohydrate moieties on herpesviridae that Aβ may target. Classical heparin-binding AMPs target viral glycoproteins, including LL-37 (Pachon-Ibanez et al, 2017) and θ and α -defensins (Hazrati et al, 2006). Immobilized HSV1 was pre-incubated with antibodies to herpesviridae glycoproteins B (gB), C (gC), D (gD), E (gE), H (gH), or G (gG) prior to incubation with conditioned CHO-CAB media.…”
Section: Resultsmentioning
confidence: 99%
“…They are important in the host's innate immune defence system. 16,38 Previous studies have reported that AMPs possess strong antimicrobial activity against gram-negative and gram-positive bacteria as well as some main pathogenic fungi. 21,39,40 In view of this, some researchers have tried to test their killing efficacy of AMPs against parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unique peptides phenol‐soluble modulins (PSM γ and PSM δ) produced by S. epidermidis can selectively inhibit the skin pathogens and help to maintain the normal skin microbiome . This multi‐directional mechanism of action of AMPs indicates that these peptides not only have low propensity to elicit microbial adaptation but also are able to neutralize exotoxins and endotoxins produced by microbes …”
Section: Amps Activity In the Skinmentioning
confidence: 99%
“…37 This multi-directional mechanism of action of AMPs indicates that these peptides not only have low propensity to elicit microbial adaptation but also are able to neutralize exotoxins and endotoxins produced by microbes. 38,39…”
Section: Antimicrobial Activity Of Ampsmentioning
confidence: 99%